Breakthrough Infection and Death after COVID-19 Vaccination: A Physics Perspective - Seyed Ali Reza Mortazavi; Abdollah Jafarzadeh; Abdolkarim Ghadimi-Moghadam; Seyed Mohammad Javad Mortazavi; Masoud Haghani; Ali Ghadimi-Moghadam; Lembit Sihver (Journal of Biomedical Physics and Engineering)
The largest universal immunization in history has occurred as a result of the COVID-19 pandemic. The developed COVID-19 vaccines have been shown to provide protection against severe forms of COVID-19 by inducing anti-spike neutralizing antibodies. It has been found that individuals who have not been vaccinated against COVID-19 were more likely to contract the virus during a period when the Delta variant was dominant, as compared to those who have received the complete dose of the vaccine, irrespective of the variant. However, there is no notable disparity in the likelihood of hospitalization, requirement for mechanical ventilation, or mortality between the two groups once infected. Nevertheless, those who are unvaccinated may require additional oxygen support. There are reports indicating unfavorable health effects, ranging from transient thyroid dysfunction to death following vaccination. In addition, some people are susceptible to SARS-CoV-2 infection despite they have immunized with the COVID-19 vaccine. Given all these considerations, several key factors should be better understood and considered to enable us to even more successfully manage future pandemics breakthrough infections. The effectiveness of physical treatment methods, e.g., Low Dose Radiation Therapy (LDRT) should be compared to pharmacological treatments.